An investigation of the changes in mechanical properties of the orofacial and neck muscles between patients with myogenous and mixed temporomandibular disorders - KARAKOÇ, ZEHRA BETÜL (TAYLOR & FRANCIS LTD, 2022)
Objective: To investigate the possible changes in the mechanical properties of the orofacial and neck muscles in patients with temporomandibular disorders (TMD). Methods: The study included a total of 98 females. Females were divided into three groups as myogenous TMD, mixed TMD, and healthy controls. The frequency (indicator of muscle tone), stiffness, and decrement (related to muscle elasticity) values of the sternocleidomastoid, upper trapezius, cervical extensor, and masseter muscles were measured using a portable myotonometer. Results: The frequency, stiffness, and decrement values of the masseter muscle were higher in the mixed and myogenous TMD groups than those of the control group (p < 0.017). The mixed TMD group had higher frequency and stiffness values in the upper trapezius muscle compared with the control group (p < 0.017). Discussion: The results suggest that the mechanical properties of the oral and neck muscles may be affected in patients with TMD.
Keywords: Temporomandibular disorders; muscle; stiffness; tone; elasticity; pain severity; neck; disability; MASSETER MUSCLE; DISABILITY-INDEX; PAIN; STIFFNESS; SYMPTOMS; SIGNS; RELIABILITY; VALIDATION; SUBGROUPS; FEATURES